The Development of a Ram Thon Activity to Enhance Balance Ability in the Elderly - Pramtun, Pannaray; Wanwichai, Rawiwan; Visuthipanich, Vanida (Journal of Cultural Analysis and Social Change, 2026)
This research is part of a larger study titled "Development of Ram Tone Activity Packages to Enhance Balance Ability Among the Elderly at Ban Suthawas Chaloem Phra Kiat, Nakhon Nayok Province." The objectives were to 1) develop Ram Tone activity packages designed to enhance balance in the elderly and 2) analyze specific Ram Tone dance movements that contribute to postural stability. The participants consisted of female elderly individuals aged 60–79 years. The researcher integrated traditional Ram Tone dance forms with physical activity principles through a four-stage development process: 1) a literature review of Ram Tone, physical activity, and muscle strengthening for balance; 2) an assessment of the target group’s physical fitness to ensure the activity packages were appropriately aligned with balance enhancement; 3) the design of Ram Tone movements based on expert recommendations; and 4) the validation of research instruments by specialists. The findings indicated that enhancing balance in the elderly should primarily focus on strengthening the lower extremities. Consequently, the researcher developed dance movements emphasizing leg transitions that align with the requirements for muscle strength and endurance. The final product consists of 4 activity packages, each containing 5 distinct movements, totaling 20 movements. The evaluation by experts revealed that all 4 packages achieved an average Item-Objective Congruence (IOC) index of 0.92, representing the highest level of appropriateness. These results suggest that the developed Ram Tone activity packages can be effectively implemented to improve balance ability among the elderly.